Anselm Hüttenbrenner in Lower Styria (1853–1858) - Motnik, Marko (De musica disserenda, 2022)
After the Styrian composer Anselm Hüttenbrenner had largely withdrawn from public life, he spent most of his time between the autumn of 1853 and the autumn of 1858 in Maribor (Marburg). In Maribor and its surroundings he found peace of mind and a closeness to nature, devoting himself intensively to compositional and pedagogical activities. He composed numerous lieder on texts by his host Ferdinand von Rast (Hilarius) plus many piano pieces, in addition to orchestral overtures and church music. The article attempts to shed light on this period in Hüttenbrenner’s life, which has not been previously studied.